2021
DOI: 10.1519/jsc.0000000000003145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High- and Low-Frequency Resistance Training on Lean Body Mass and Muscle Strength Gains in Untrained Men

Abstract: Franco, CMC, Carneiro, MAS, de Sousa, JFR, Gomes, GK, and Orsatti, FL. Influence of high- and low-frequency resistance training on lean body mass and muscle strength gains in untrained men. J Strength Cond Res 35(8): 2089–2094, 2021—The aim of this study was to investigate whether high-frequency resistance training (HFRT) performs better in lean body mass (LBM) and muscle strength gains when compared with low-frequency resistance training (LFRT). Eighteen untrained males (height: 1.76 ± 0.05 m, body mass: 78.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, controversial results are obtained in studies comparing the effect of split vs. full-body routines on muscle growth and strength gains. For example, similar gains in muscle mass and strength performance have been reported after split and full-body routines between untrained (10,13,25) and trained (12,22) people. By contrast, other studies reported that full-body routines may be more effective at improving cross-sectional area than split routines (34,39) .…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…However, controversial results are obtained in studies comparing the effect of split vs. full-body routines on muscle growth and strength gains. For example, similar gains in muscle mass and strength performance have been reported after split and full-body routines between untrained (10,13,25) and trained (12,22) people. By contrast, other studies reported that full-body routines may be more effective at improving cross-sectional area than split routines (34,39) .…”
Section: Introductionmentioning
confidence: 56%
“…In addition, in the leave-one-out meta-analysis test, no study was found that significantly altered the direction or statistical value of the effect on the variables of 1RM bench press, 1RM lower-limb, and elbow flexors cross-sectional area (see Table 2, Supplemental Digital Content, http://links.lww.com/JSCR/A477). However, in the vastus lateralis cross-sectional area, the study by Schoenfeld et al (34) modified the direction of the effect without significant changes ( p = 0.972), and in the lean body mass, the study by Franco et al (10) also modified the direction of the effect without significant changes ( p = 0.972).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, performing the same exercises during the RT program allows the adjustment of the other acute prescription variables, such as intensity and volume, besides providing a faster and more pronounced workload (e.g., volumeload) progression. However, the influence of volume-load on the muscle strength response is still not completely elucidated because some studies show similar results for this capacity even with different volume-load (14,15,29). Given all the information mentioned above, it is not yet known whether there is a difference between a routine RT that maintains the exercises fixed or varied on muscle strength because both strategies have possible advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%